Egil's saga : traditional evidence for Brúnanburh compared to literary, historic and archaeological analyses - Kirby, John R., (Access archaeology., 2019)
Was Egil's Saga 'written' by Snorri Sturluson or by more than one person? Was it embellished by Snorri or others? Where did the Brúnanburh traditions come from? Is it accurate enough to be used as a historic source - a factual reference? This study aims to identify the incongruities within this saga demonstrating a correct analysis.